Occurrence of Pediculus humanus capitis in Relation to their Personal Hygiene and Social Behaviour Among the Children in Dhaka City - Karim, Tahmina; Musa, Sharmin; Khanum, Hamida; Mondal, Dinesh (Bangladesh Journal of Zoology, 2016)
Abstract not available Bangladesh J. Zool. 43(2): 327-332, 2015